Entrepreneurial investment evaluation decision-making: A focus on venture capitalists, business angels and early-stage entrepreneurs in South Africa - Boris Urban; Marco Antonio Moreno (The Journal of Entrepreneurial Finance (JEF), 2022)
Business angels (BAs) and venture capitalists (VCs) are important sources of finance for entrepreneurs in emerging markets for raising start-up and growth capital. Recognising that entrepreneurial investment evaluation decision-making is a highly complex process, and that there are limited studies focused on evaluation criteria used by both BAs and VCs', this article undertakes an empirical investigation by identifying, classifying and statistically testing the rank importance of investment criteria in South Africa from an early-stage entrepreneurial perspective. Results indicate that the rank importance for the different investment criteria is relatively similar for VCs and BAs, and the only ranking difference observed was on the team preparedness and team attributes, relevant for early-stage entrepreneurs. An empirical study of this nature is important as unique insights emerge from testing multiple investment evaluation criteria used by VCs, BAs and early-stage entrepreneurs in an African emerging country context.
Keywords: G21; G32; L26; O4; M1; M13; 650; Venture Capitalists; Business Angels; Entrepreneurial Decision-Making; Investment Evaluation Criteria; Early-Stage Entrepreneurs; South Africa